2022
DOI: 10.22541/au.164864286.63566927/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 in children with cancer and continuation of cancer-directed therapy during the infection- A tertiary care center experience from India

Abstract: 1 Background and Objective Coronavirus disease-2019 (COVID-19) or its complications in children with cancer were not increased as compared to normal children in earlier reports. However, continuing intensive treatment during ongoing COVID-19 infection has not been studied systematically. We report a single tertiary center experience on COVID-19 in children with cancer and continuation of cancer-directed therapy in them. 2 Methods Children ≤15years on active cancer treatment detected with COVID-19 until Septemb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Authors of a Polish study concluded that the SARS-CoV-2 infection did not increase mortality immediately in patients with cancer, but it was associated to higher chemotherapy rates discontinuation ( 45 ). Similar results were obtained by Parambil et al and the authors concluded that chemotherapy shouldn't be interrupted upon obtaining a positive test identifying SARS-CoV-2 ( 46 ). A pending question is if chemotherapy can be continued in patients with severe disease and improve recommendations of treatment for patients with cancer and COVID-19 ( 47 ).…”
Section: Discussionsupporting
confidence: 83%
“…Authors of a Polish study concluded that the SARS-CoV-2 infection did not increase mortality immediately in patients with cancer, but it was associated to higher chemotherapy rates discontinuation ( 45 ). Similar results were obtained by Parambil et al and the authors concluded that chemotherapy shouldn't be interrupted upon obtaining a positive test identifying SARS-CoV-2 ( 46 ). A pending question is if chemotherapy can be continued in patients with severe disease and improve recommendations of treatment for patients with cancer and COVID-19 ( 47 ).…”
Section: Discussionsupporting
confidence: 83%